2018
DOI: 10.1063/1.5023965
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation and antioxidant activity potency of the extract of Garcinia lateriflora Blume var. javanica Boerl leaf

Abstract: Preparation and characterization of cross-linked excipient of coprocessed xanthan gumacacia gum as matrix for sustained release tablets AIP Conference Proceedings 1933, 030009 (2018 Abstract. Garcinia lateriflora leaves extract of the family Guttiferae has been known to have excellent antioxidant activity. The objective of the study was to determine the antioxidant effect of the n-hexane, ethyl acetate and methanol extracts of G. lateriflora leaves extract. The antioxidant activity was determined by 1,1-diphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Our findings showed that polar fractions, in current study, exhibited highest phenolic and flavonoid content. These results are in accordance with previous data that showed that phenolic compounds being polar in nature are found in polar fractions [34]. In current study, ENBF exhibited highest phenolic content (143.26±2.65 mg/g GA) followed by ENCr (125.6±1.32 mg/g GA), ENAF (96.53±2.01 mg/g GA), ENCF (38.27±3.21 mg/g GA) and ENHF (15.49±1.92 mg/g GA) as shown in Fig.…”
Section: Resultssupporting
confidence: 94%
“…Our findings showed that polar fractions, in current study, exhibited highest phenolic and flavonoid content. These results are in accordance with previous data that showed that phenolic compounds being polar in nature are found in polar fractions [34]. In current study, ENBF exhibited highest phenolic content (143.26±2.65 mg/g GA) followed by ENCr (125.6±1.32 mg/g GA), ENAF (96.53±2.01 mg/g GA), ENCF (38.27±3.21 mg/g GA) and ENHF (15.49±1.92 mg/g GA) as shown in Fig.…”
Section: Resultssupporting
confidence: 94%
“…This could be due to a compound found in ethanol extract that, while being in a solvent with different polarity, tends to work in synergy. 33 The antioxidant activity test on the 96% ethanol extract, water, ethyl acetate, and n-hexane fractions inhibited the DPPH radicals with IC50 values of 44.86, 45.31, 40.48, and 39.35 µg/mL, respectively compared to the Trolox 3.49 µg/mL (Table 2). Based on this observation, the less non-polar the solvent used, the lower the IC50 value.…”
Section: Resultsmentioning
confidence: 99%
“…Because the ABTS technique is light-sensitive, even the synthesis of ABTS•requires a 12-to 16-hour incubation period in the dark. 33 The antioxidant testing with the ABTS method is proportionate to DPPH, specifically the nhexane fraction, which has a very strong antioxidant activity (< 50 µg/mL). Both the DPPH and ABTS methods for determining the antioxidant are in vitro procedures.…”
Section: Resultsmentioning
confidence: 99%
“…A blank mixture of DPPH and ethanol was used as a control. The percentage of DPPH radical scavenging was measured using the following equation: 23,25…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%